1991
DOI: 10.1016/1010-7940(91)90030-n
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and surgical treatment of ectopic atrial tachycardia

Abstract: Eighty-two patients with ectopic atrial tachycardia (EAT) were subjected to radical closed heart surgery (without cardiopulmonary bypass). The age of the patients ranged from 1 to 51 years. Permanent EAT was present in 19 patients, incessant EAT in 14, and paroxysmal EAT in 49 patients. Preoperative electrophysiological study included computed analysis of the P wave vector. Ectopic foci were established in the right atrium in 34 patients, in the left atrium in 11, in the interatrial septum in 32, and extracard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This provocative observation is consistent with different mechanisms of lesion formation, with a less clear relationship between cryoablation lesion size and extent of endothelial cell injury. A plausible clinically relevant corollary to this finding is that interventions requiring more extensive tissue destruction, such as procedures for 28 -32 In 118 patients undergoing surgical ablation of reentrant supraventricular arrhythmias 30 and 82 patients with ectopic atrial tachycardia, 31 no thromboembolic complications were reported. In a series of 14 patients undergoing the maze procedure for atrial fibrillation, 1 patient with Yamagushi disease had a small pulmonary embolus.…”
Section: Cryoenergy Ablation and Thromboembolic Complicationsmentioning
confidence: 99%
“…This provocative observation is consistent with different mechanisms of lesion formation, with a less clear relationship between cryoablation lesion size and extent of endothelial cell injury. A plausible clinically relevant corollary to this finding is that interventions requiring more extensive tissue destruction, such as procedures for 28 -32 In 118 patients undergoing surgical ablation of reentrant supraventricular arrhythmias 30 and 82 patients with ectopic atrial tachycardia, 31 no thromboembolic complications were reported. In a series of 14 patients undergoing the maze procedure for atrial fibrillation, 1 patient with Yamagushi disease had a small pulmonary embolus.…”
Section: Cryoenergy Ablation and Thromboembolic Complicationsmentioning
confidence: 99%
“…Cryoablation of the ectopic focus, with or without cardiopulmonary bypass, is effective (Bredikis et al, 1991). However, it should be realized that epicardial cryoablation may not produce a transmural lesion in the normothermic beating heart (Doll et al, 2003).…”
Section: Ectopic Focus (Automatic) Atrial Tachycardiasmentioning
confidence: 97%
“…A combination of cryoablation and resection might be effective in some cases (Graffigna et al, 1992). For multiple ectopic focal tachycardias, more extensive techniques could be required, such as right or left atrial isolation or pulmonary vein isolation (Bredikis et al, 1991;Doll et al, 2003).…”
Section: Ectopic Focus (Automatic) Atrial Tachycardiasmentioning
confidence: 97%